ANALISIS VISUAL BALIHO PEMILU CALON LEGISLATIF 2014 DAERAH PEMILIHAN DENPASAR SELATAN - I Gusti Nyoman Widnyana; Ni Nyoman Sri Witari (Universitas Pendidikan Ganesha, 2015)
The aim of this studyis to identify the billboard of legislative candidates 2014 in the elections area the south Denpasar. Especially, it aims to know the weakness of the billboard design. To identify its weakness, selected nine pieces of billboard taken from nine different villages where the billboard have a problem in the design. Then, those four billboards that have the greatest problem in design are taken to be identified. Data were collected through the observation by taking the picture of the billboard of legislative candidates. Then, the data is analyzed descriptively and qualitatively. The results showed that the weakness of the billboard candidates in general is on the designs. It shows that the designed does not follow the rules of the science of Visual Communication Design. Because of that, it is necessary to give the examples of better designs. So whatever the purpose of making the billboards can be in accordance whit what is expected.Keywords: Election Billboard,Visual Analysis, South Denpasar.